P-093 Always Seen But Often Overlooked—Shortfalls in Skin Protective Practices Counseling for IBD Patients. (March 2016) - Baig, Kamal; Chablaney, Shreya; Caldis, Matthew; Waseem, Najeff; Nassereddine, Samah; Zhang, Jennie; Dougherty, Timothy; Borum, Marie
Abstract : Background: Patients with inflammatory bowel disease (IBD) have many unique health care needs. There is increasing evidence of an elevated baseline risk of skin cancer among individuals with IBD. This elevated risk may be related to the underlying disease, the use of certain immunomodulating medications, or the combination of the 2. It is recommended that individuals with IBD be counseled about preventative measures to reduce their risk of skin cancer. This study aims to examine physician counseling practices regarding skin cancer risk and prevention for IBD patients. Methods: A retrospective review was completed using an electronic medical record of consecutive IBD patients who presented for surveillance colonoscopy at an urban academic medical center during a 1-year period. Data regarding patient ethnicity, IBD type and extent, current treatment regimen, documentation of counseling regarding skin cancer and preventive practices, and colonoscopic findings were compiled in a database created with Microsoft Excel. Patient confidentiality was maintained. The study was approved by the university institutional review board. Statistical analysis was performed using Fisher's exact test, with statistical significance set at P < 0.05. Results: There were 136 IBD patients included, 57 (41.9%) were male and 79 (58.1%) were female. Sixty-eight patients were Caucasian (50.0%), 34 (25.0%) African American, 8 (5.9%) Latino, 14 (10.3%) were of "other" ethnicity, and 12 (8.8%) were of unknown ethnicity. 78 had ulcerative colitis and 58 had Crohn's disease. Of the 136 IBD patients, 46 (34%) were counseled on skin cancer preventative measures or referred to a dermatologist. Twenty-seven (39.7%) Caucasian and 8 (23.5%) African American patients were counseled. 28 (35.9%) ulcerative colitis patients and 18 (31.0%) Crohn's patients were counseled. There was no statistically significant difference in the rate of skin protective counseling based on race/ethnicity ( P = 0.2555) or disease type ( P = 0.5869). Conclusions: Compared to the general population, IBD patients are at increased risk for the development of skin cancer. It is recommended that these patients receive counseling on skin protective practices. In this study only one-third of medical records showed documentation of counseling or dermatology referral. The shortfall in counseling or referral practices may be attributed to the complex nature of care required for IBD patients, decrease awareness or lack of clear documentation. While this study is limited due to size, the data should serve as a reminder to include counseling for skin protective in IBD patients. Efforts to increase awareness of health care providers and patients about skin cancer risks are important.